ANALISIS KAUSALITAS ANTARA MIGRASI, PENGANGGURAN, DAN KEMISKINAN DI INDONESIA - Anna Willia Glorina; Sri Ulfa Sentosa (Universitas Negeri Padang, 2019)
This study aims to determine whether there is a causal relationship between migration, unemployment and poverty in Indonesia. The data used are secondary data in the form of panels with a period of time from 2013 to 2017, with the technique of collecting documentation data and library studies obtained from relevant institutions and agencies. The variables used are migration, unemployment, and poverty. The research method used is Vector Auto Regression (VAR). The results show that: (1) There is no causality between migration and unemployment but there is only a one-way relationship between unemployment and migration (2) There is a causality between migration and poverty (3) There is a causality between unemployment and poverty.